2019
DOI: 10.1007/s40429-019-00280-0
|View full text |Cite|
|
Sign up to set email alerts
|

Gambling and Social Cognition: a Systematic Review

Abstract: Purpose of Review The aim of this article was to review current research regarding social cognition (SC) in gambling disorder (GD), to (i) compile and synthetize the current state of existing literature on this topic, and (ii) propose cognitive remediation therapy approaches focused on SC for clinicians. Recent Findings It is well known that disordered gamblers show impairment regarding non-social cognitive functions such as inhibition, attention, and decision-making. Furthermore, patients with substance use d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 87 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…148 This is because the ingestion of psychoactive substances alters neurocognitive functioning and may influence the evaluation of cognitive mechanisms underlying addiction in those with substance use disorders. 149 Finally, this study explores cognitive functions that are still underexplored, such as social cognition and metacognition 58,59 and will provide new results examining functions that have produced mixed results, such as flexibility or decision making. 53 This will permit a better understanding of common and specific neurocognitive patterns in several BAs and improve the understanding of the factors that trigger and maintain BAs and addictions in general.…”
Section: Expected Results and Clinical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…148 This is because the ingestion of psychoactive substances alters neurocognitive functioning and may influence the evaluation of cognitive mechanisms underlying addiction in those with substance use disorders. 149 Finally, this study explores cognitive functions that are still underexplored, such as social cognition and metacognition 58,59 and will provide new results examining functions that have produced mixed results, such as flexibility or decision making. 53 This will permit a better understanding of common and specific neurocognitive patterns in several BAs and improve the understanding of the factors that trigger and maintain BAs and addictions in general.…”
Section: Expected Results and Clinical Implicationsmentioning
confidence: 99%
“…53 A review of the literature showed that attentional processes also seem to be biased, with an attentional bias towards gambling cues highlighted in GbD patients. 54 Additionally, some cognitive functions, such as social cognition (ie, all functions that permit the development and maintenance of relationships with others, from basic functions such as the detection of emotions to more complex ones such as the understanding of irony), [55][56][57] are still underexplored, 58,59 To our knowledge, only one study has explored social cognition in those with GbD and suggested specific alterations in nonverbal emotional processing. 60 Overall, despite the growing literature exploring neurocognition in those with GbD, further research is still needed.…”
Section: Cognitive Functioning In Addictionsmentioning
confidence: 99%
“…There is evidence of impaired cognitive empathy and emotion recognition problems in persons with eating disorders, such as Anorexia Nervosa and BED (Kerr-Gaffney et al, 2019;Saure et al, 2022), and emotion dysregulation can trigger food addiction symptoms (Pivarunas & Conner, 2015). Multiple studies have reported significant deficits in affective and cognitive empathy in gambling behaviors (Hurel et al, 2019;Wu et al, 2022). A cross-generational study of video gamers revealed a negative association between the amount of time spent on games and cognitive empathy, as game playing reduces the need to infer mental states, thereby lessening the need to activate one's social brain (Shin & Ahn, 2013).…”
Section: Cognitive Empathy (Emotion Recognition and Perspective-taking)mentioning
confidence: 99%
“…Gambling disorder (GD) has been defined as a persistent and recurrent problematic gambling pattern, which leads to clinical impairment or distress ( 1 ). According to the dual-processing model of decision-making ( 2 , 3 ), individuals with GD may have deficits in both the impulsive system and the reflective system ( 4 , 5 ), and imbalance between these two neurocognitive systems may lead them gradually to become addicted to gambling ( 6 , 7 ). This study aimed to address the knowledge gap regarding the association between empathy and GD from the neurocognitive perspective ( 8 ).…”
Section: Introductionmentioning
confidence: 99%